THE INFLUENCE OF ENVIRONMENTAL SANITATION ON CLEAN AND HEALTHY LIVING BEHAVIOR OF CHILDREN AGED 4-6 YEARS IN SEMARANG CITY - Astuti, Aulia Tri; Windiarti, Rina (BELIA: Early Childhood Education Papers, 2019)
This study aims to determine whether there is an influence of environmental sanitation on clean and healthy living behavior (PHBS) of children aged 4-6 years in RW 3 Kampung Pelangi. This research is a quantitative research with a type of survey research and quantitative descriptive design, as well as a questionnaire as a measurement tool. The population of this study is 48 children aged 4-6 years in RW 3 Kampung Pelangi, Randusari Village, in South Semarang District. Sampling is taken with a Nonprobability Sampling-Purposive Sampling technique of 32 children. Analysis of the data is simple linear regression analysis. The results show that based on the results of data from the Coefficients table as the output of a simple linear regression analysis, the R Square value is 0.374. Thus it means that environmental sanitation had a contribution of 37.4% in clean and healthy living behavior (PHBS) of children aged 4-6 years in RW 3 Kampung Pelangi, while the other 62.6% is explained by other variables not examined. The conclusion of this study is that there is an influence between environmental sanitation and healthy living behaviors in children aged 4-6 years in Kampung Pelangi, Randusari Village, South Semarang District, Semarang City. This is evidenced by the significance value of 0.00, which means 0.00 < 0.05. Suggestions related to this research are the efforts to cleanliness and personal and environmental health for children should be intensified, especially the community members as household organizers through socialization, counseling, or other health promotion activities so that they are aware, aware, able, and willing to be improved and maintaining environmental sanitation followed by PHBS.